Divinas caixas e suas histórias: as filhas de santo/caixeiras e suas representações do Divino em Porto Franco/MA - SANTOS, Bruno Barros dos (2022)
The Feast of Divino Espírito Santo is present in practically all of the Brazilian territory, but it is in the State of Maranhão that this devotion comes close to the terreiros of Umbanda, Terecô and Tambor de Mina (LEAL, 2019, 2017; BARBOSA, 2006; FERRETTI, 1996). The problem that guides this research is how caixeiras from Porto Franco/MA (also being the daughters of saints at Terecô) produce representations of the Divine Espírito Santo and how they use it in their daily lives. I mean, how the representations of the Divine mark their life stories, their practices and representations of the world. The concept of representation is central to this analysis, as references are based on Chartier (2011; 2002; 1991) and Machado (2011). Methodologically, I rely on Debert (1986), Levi (1998) and Portelli (2016) on the use of oral history and life stories. The life stories of the interlocutors accessed by their narratives refer to religious and historical trajectories in Maranhão cities. This dialogue made even at graduation with virtual and presential meetings. The life trajectory of these women, who are sometimes daughters of saints/caixeiras, and sometimes caxeiras/daughters of saints, points too to a strength that comes from blackness, ancestry, in the victory and continuation of their struggles.